2007
DOI: 10.1021/es0705386
|View full text |Cite
|
Sign up to set email alerts
|

Formation of N-Nitrosodimethylamine (NDMA) from Humic Substances in Natural Water

Abstract: N-nitrosodimethylamine (NDMA)formation in chloraminated Iowa River water (IRW) is primarily attributed to reactions with natural organic matter (NOM) generally classified as humic substances. Experiments were conducted to determine the contribution of various NOM humic fractions to the NDMA formation potential (NDMA FP) in this drinking water source. NOM was concentrated by reverse osmosis (RO) and humic fractions were obtained by a series of resin elution procedures. Mass balances showed that nearly 90% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(54 citation statements)
references
References 25 publications
4
50
0
Order By: Relevance
“…On the other hand, Gerecke and Sedlak [53] and Chen and Valentine [52,61] have shown that chloramination of natural organic matter (NOM) is responsible for the formation of significant amounts of NDMA. According to Chen and Valentine [52], the oxidation of natural organic matter by chloramines is the ratedetermining step in formation of NDMA.…”
Section: Precursors Of Ndma In Drinking Water Technologymentioning
confidence: 99%
“…On the other hand, Gerecke and Sedlak [53] and Chen and Valentine [52,61] have shown that chloramination of natural organic matter (NOM) is responsible for the formation of significant amounts of NDMA. According to Chen and Valentine [52], the oxidation of natural organic matter by chloramines is the ratedetermining step in formation of NDMA.…”
Section: Precursors Of Ndma In Drinking Water Technologymentioning
confidence: 99%
“…In previous studies, different wavelengths (e.g., 254 nm [44], 272 nm [45], 280 nm [46]) have been used to determine the SUVA value. Hur et al [47] reported that SUVA determined near to 250 nm is correlated with aromatic organic compounds.…”
Section: Model(s) Developmentmentioning
confidence: 99%
“…These include both heterogeneous organic mixtures such as humic substances found in the natural environment [31] and some specific organic compounds containing the amine functional group such as dimethylamine, triethylamines, and dimethylaminobenzene ( Fig. 1).…”
Section: Ndma Precursorsmentioning
confidence: 99%